Inhibited phenol ionization in reverse micelles: Confinement effect at the nanometer scale - Silva, Oscar Fernando (2012)
We found that the absorption spectra of 2-acetylphenol (2-HAP), 4-acetylphenol (4-HAP), and p-nitrophenol (p-NPh) in water/sodium 1,4-bis(2-ethylhexyl)sulfosuccinate (AOT)/n-heptane reverse micelles (RMs) at various W 0 (W 0=[H 2O]/[surfactant]) values studied changed with time if -OH ions were present in the RM water pool. There is an evolution of ionized phenol (phenolate) bands to nonionized phenol absorption bands with time and this process is faster at low W 0 values and with phenols with higher bulk water pK a values. That is, in bulk water and at the hydroxide anion concentration used, only phenolate species are observed, whereas in AOT RMs at this fixed hydroxide anion concentration, ionized phenols convert into nonionized phenol species over time. Furthermore, we demonstrate that, independent of the -OH concentration used to prepare the AOT RMs, the nonionized phenols are the more stable species in the RM media. We explain our results by considering that strong hydrogen-bonding interactions between phenols and the AOT polar head groups result in the existence of only nonionized phenols at the AOT RM interface. The situation is quite different when the phenols are dissolved in cationic benzyl-n-hexadecyldimethylammonium chloride RMs. Therein, only phenolates species are present at the -OH concentrations used. The results clearly demonstrate that the classical definition of pH does not apply in a confined environment, such as in the interior of RMs and challenge the general idea that pH can be determined inside RMs. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.